Assessing the Relationship Between Gut Microbiota and Bone Mineral Density - Cheng, Shiqiang; Qi, Xin; Ma, Mei; Zhang, Lu; Cheng, Bolun; Liang, Chujun; Liu, Li; Li, Ping; Kafle, Om Prakash; Wen, Yan; Zhang, Feng (Frontiers in Genetics, 2020)
Background: Recent study demonstrate the comprehensive effects of gut microbiota on complex diseases or traits. However, limited effort has been conducted to explore the potential relationships between gut microbiota and BMD. Methods: We performed a polygenetic risk scoring (PRS) analysis to systematically explore the relationships between gut microbiota and body BMD. Significant SNP sets associated with gut microbiota were derived from previous genome-wide association study (GWAS). In total, 2,294~5,065 individuals with BMD values of different sites and their genotype data were obtained from UK Biobank cohort. The gut microbiota PRS of each individual was calculated from the SNP genotype data for each study subject of UK Biobank by PLINK software. Using calculated PRS as the instrumental variables of gut microbiota, Pearson correlation analysis of individual PRS values and BMD values was finally conducted to evaluate the possible association between gut microbiota and target trait. Results: In total, 31 BMD traits were selected as outcome to assess their relationships with gut microbiota. After adjusted for age, sex, body mass index and the first 5 principal components (PCs) as the covariates using linear regression model, pelvis BMD (P=0.0437) showed suggestive association signal with gut microbiota after multiple testing correction. Conclusion: Our study findings support the weak relevance of gut microbiota with the development of BMD.